Tindak Tutur Ekspresif dalam Film Gara-Gara Warisan (2022) (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2026)
This research intends to outline the structure, purpose, and practical significance of expressive speech acts in the 2022 movie Gara-gara Warisan. This research utilizes a qualitative descriptive approach with content analysis to investigate conversations featuring expressive speech acts according to Searle's theory. Data was gathered using data collection methods executed in multiple phases; (1) viewing the film in its entirety; (2) documenting dialogues pertinent to the research focus; and (3) analyzing the significance of the dialogues based on the theory of expressive speech acts that inform the dialogues. The study results reveal seven categories of expressive speech acts: expressions of gratitude, apologies, congratulations, compliments, condolences, blame, and anger. A total of 47 cases of expressive speech acts were noted, which comprised 3 gratitude expressions, 6 apology expressions, 5 congratulations expressions, 5 praise expressions, 5 condolences expressions, 10 blame expressions, and 13 anger expressions. These results show that expressive dialogues in films clearly illustrate the emotional state, sentiments, and social dynamics among characters, particularly in the context of family conflicts. This research aims to enhance pragmatic analysis, especially concerning expressive speech acts in audiovisual media, and to act as a reference for studies on speech act analysis.